Efectos del riego por goteo y del riego por surcos en la fenologia y el rendimiento del algodon - Mateos, L.=700 1 Berengena, J.; Soriano, M.A.; Orgaz, F.; Tellez, A.; Fereres, E.
(Es, En)
ilus., 18 ref.
Keywords: GOáYPIUM HIRSUTUM; ALGODON; RIEGO POR GOTEO; NECESIDADES DE AGUA; EVAPOTRANSPIRACION; ESPAÑA